Studi Perbandingan Performa Ketidakberaturan Horizontal Bangunan Terhadap Beban Gempa - Andra Akmal Maulidani; Dzul Fikri Muhammad; Muhammad Abdul Rahman; Edi Santoso (Universitas Islam Raden Rahmat, Malang, 2024)
Indonesia is located on 3 large tectonic plates, making the Indonesian region vulnerable to earthquakes. To overcome this, it is necessary to plan buildings that are earthquake resistant. High population growth has resulted in many different models of tall buildings. These diverse building models have led to the emergence of irregular building designs, both horizontally and vertically. This irregularity can affect the results of structural analysis of earthquake loads. This research discusses the effect of horizontal irregularities in buildings on earthquake loads with the results of research that regular buildings have structural stiffness properties that are relatively stiffer than irregular buildings. In addition, irregularities also result in smaller deviation values ​​between floors in the X direction and larger in the Y direction when compared to irregular.